Hypertension prevention campaign through blood pressure screening and lifestyle education - Yuliana Yuliana (Bakti Nusantara Pengabdian Masyarakat Indonesia, 2026)
Background: Hypertension remains a major public health concern because it is often asymptomatic in its early stages and may lead to serious cardiovascular complications if left undetected and uncontrolled. Community-based promotive and preventive strategies, particularly blood pressure screening and lifestyle education, are essential to improve early detection and strengthen public awareness of modifiable risk factors. Objective: This community service program aimed to enhance early detection of hypertension and improve community knowledge regarding hypertension prevention through blood pressure screening and lifestyle education. Methods: A community-based participatory promotive-preventive approach was applied involving adults and older adults. The program integrated blood pressure screening using calibrated digital devices, group health education, interactive discussions, and individual health consultations. Educational content emphasized hypertension risk factors, healthy dietary practices, regular physical activity, stress management, smoking reduction, and moderation of caffeine intake. Program evaluation included respondent characteristics, blood pressure screening results, and changes in participants’ knowledge before and after the educational intervention. Results: A total of 60 participants were involved, most of whom were aged 36–55 years (46.7%), female (60.0%), had secondary education (45.0%), and worked in the informal sector (50.0%). Screening results showed that 35.0% had normal blood pressure, while 30.0% were classified as prehypertensive, 21.7% as grade 1 hypertensive, and 13.3% as grade 2 hypertensive. Several behavioral risk factors were also identified, including physical inactivity (51.7%), routine coffee consumption (43.3%), and smoking (30.0%). Knowledge outcomes improved markedly after education, with the proportion of participants in the good knowledge category increasing from 26.7% before the intervention to 70.0% afterward. Conclusion: Blood pressure screening combined with lifestyle education was effective in improving early detection of hypertension and strengthening community knowledge regarding risk factors and preventive behaviors. Sustained implementation, broader community coverage, and medium-term behavioral monitoring are recommended to optimize the long-term impact of hypertension prevention programs.